Gender, Risk-Taking Propensity and Culture of Entrepreneurs at Small and Medium Enterprises in Gauteng - Garg, Ajay K; Letsolo, Peter (Journal of Economics and Behavioral Studies, 2016)
This study analyzed the risk-taking propensity amongst the four cultural groups and its impact on the business performance, from a sample of Small and Medium Enterprises (SMEs) within the Gauteng Province of South Africa. The data was collected using two sets of questionnaire measuring risk taking propensity and perceived business performance. 83 responses were returned from 400 respondents. The results indicate that male on average show higher risk taking, while difference in risk taking propensity between male and female was not statistically significant. A very weak or no correlation between risk taking and business performance scores for both the genders were found, indicating that gender and culture does not play a role in the relationship between risk taking and business performance. However study found that there was significant difference in risk taking behavior by different culture groups, Zimbabweans were the highest risk takers, while Chinese, Pakistanis and South Africans differed in their risk taking behavior.